Pengaruh Kepemimpinan Kepala Sekolah dan Kompetensi Guru Terhadap Prestasi Belajar Siswa SMPN 4 Pujud Kab. Rokan Hilir Prov. Riau - Tengkoe Irawan; Mira Rosmala (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2025)
This research aims to find out how much influence the principal's leadership and teacher competence have on student learning achievement at SMPN 4 Pujud Kab. Rokan Hilir Prov. Riau. In the validity and reliability test, it can be seen that the results are valid and reliable. In the partial test (t test) it can be seen that there is an influence between the principal's leadership and student learning achievement as proven by t-count (2.114) > t-table (2.0003), teacher competence on student learning achievement as proven by t-count (3.356) > t -table (2.0003), simultaneous test (F test) can be seen that there is a simultaneous relationship between the principal's leadership and teacher competence on student learning achievement as proven by F-count (6.454)>F-table (3.25). And the Determination Test (R2) was 0.177 (17.7%) that the principal's leadership and teacher competence would have a positive influence on student learning achievement while the remaining 0.823 (82.3%) was explained by other factors not examined in this research.